PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS XII MIPA SMA NEGERI 8 PADANG - Safwan, Zahra Amaliyya; Mirna, Mirna (Departemen Matematika, 2024)
The goal of learning mathematics is problem-solving proficiency. In fact, this ability is limited. Initial assessments provided this data. To address this skill gap, the Think Talk Write Co-operative Model engages students in peer conversation and problem solving. The quasi-experimental study employed Posttest Only Control Group Non-equivalent Control Group Design. Simple random sampling was used. Experimental class XII MIPA 4 and control class 3. Think Talk Write cooperative learning outperforms direct learning with a P-value of 0.004, below the significance level of 0.05.Keywords – Mathematical Problem-solving, Think Talk Write